2021
DOI: 10.31557/apjcp.2021.22.8.2501
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Survival with Current Therapies and New Targeted Treatments: A Comprehensive Update from the Srinagarind Hospital-Based Cancer Registry from (2013 to 2017)

Abstract: Background: Lung cancer (LC) is a common malignancy and leading cause of cancer death worldwide and in Thailand. An update on LC survival factors after diagnosis at Srinagarind Hospital is needed. Methods: We conducted a retrospective cohort study, and the data were sourced from the Srinagarind Hospital-Based Cancer Registry. All LC cases were diagnosed between January 1, 2013, and December 31, 2017, and followed up until November 30, 2019. Cases of LC (ICD-O-3) numbered 2,149, but only those with coding C34.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The prevalence of LUAD is increasing annually and is about to become the main subtype of NSCLC [ 2 ]. Despite improvements in early diagnosis, patients with LUAD still have a low 5-year overall survival rate and unsatisfactory recurrence rate [ 3 , 4 ]. Currently, the clinical treatment protocols for LUAD mainly include drugs and radiotherapy; however, they are often prone to tolerance in patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of LUAD is increasing annually and is about to become the main subtype of NSCLC [ 2 ]. Despite improvements in early diagnosis, patients with LUAD still have a low 5-year overall survival rate and unsatisfactory recurrence rate [ 3 , 4 ]. Currently, the clinical treatment protocols for LUAD mainly include drugs and radiotherapy; however, they are often prone to tolerance in patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 Emerging evidences have demonstrated that hyperactivation of oncogenes and/or low expression of tumor suppressor genes obviously promotes the occurrence and development of LUSC. 2,4,14 In view of the fact that LUSC lacks targeted agents available compared with lung adenocarcinoma, 3,15 identification of biomarkers that are involved in the occurrence and development of cancer cells may provide helpful candidates for clinical outcome prediction and clinical targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Two decades later, there are 71 small molecular kinase inhibitors approved by the U.S. FDA [ 23 ]. For advanced NSCLCs harboring activating EGFR mutations, an EGFR-TKI provides a superior survival benefit compared with platinum-based chemotherapy [ 24 , 25 ]. Osimertinib, another potent EGFR-TKI, was shown to be highly active in patients who had resistance to previous EGFR inhibitors [ 26 ].…”
Section: Discussionmentioning
confidence: 99%